Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Variability in cadmium stress and accumulation in quinoa: Potential role of crop domestication and selection in mediating differences in resilience and uptake - Alejandro Rodriguez-Sanchez; Martha Jimenez-Castaneda; Timothy Filley; David Brenner; Dennis Macedo; Victor H. Casa; Lori Hoagland (Science of The Total Environment, 2026)

Integration of microbial bioreactors and Lemna minor cultivation for sustainable treatment of dairy processing wastewater - Éamonn Walsh; Lekha Menon Margassery; Alejandro Rodriguez-Sanchez; David Wall; Paul Bolger; Marcel A.K. Jansen; Niall O'Leary (Journal of Water Process Engineering, 2024)

A metabolomics perspective on the effect of environmental micro and nanoplastics on living organisms: A review - Leilei Zhang; Pascual García-Pérez; Barbara Muñoz-Palazon; Alejandro Gonzalez-Martinez; Luigi Lucini; Alejandro Rodriguez-Sanchez (Science of The Total Environment, 2024)

Treatment of dairy wastewater using intermittent-aeration sequencing batch reactor at pilot-scale - Alejandro Rodriguez-Sanchez; Beatriz Gil-Pulido; Peter Leonard; William Finnegan; Xinmin Zhan; Alan D.W. Dobson; Niall O'Leary (Bioresource Technology Reports, 2024)

Carrot genotypes differentially alter soil bacterial communities and decomposition of plant residue in soil - Narda J. Triviño; Alejandro Rodriguez-Sanchez; Timothy Filley; James J. Camberato; Micaela Colley; Phillip Simon; Lori Hoagland (Plant and Soil, 2023)
Purpose Farmers need alternative approaches to manage nitrogen (N) that meet crop needs while reducing loss to the environment. Identifying crop genotypes that promote decomposition of organic materials and understanding the potential mechanisms responsible could help address this challenge. Consequently, we aimed to 1) determine whether carrot genotypes differ in their potential to facilitate organic matter decomposition in soil, and 2) identify bacterial taxa that are stimulated by carrot roots, and thus could play a role in these processes. Methods We grew five genotypes expected to differ in N use efficiency in a nutrient-poor soil amended with 15 N-enriched corn residue, tracked changes in carbon (C) and N pools, quantified microbial activity and bacterial community composition, and predicted the potential expression of microbial genes involved in soil C and N cycles. Results Experimental genotype 8503 had the greatest capacity to promote decomposition of corn residues. This genotype had the highest % of N from the corn residue in its taproots and on average, promoted higher b-glucosidase activity in soils. Distinct bacterial communities from the families Micromonosporaceae , Chromatiaceae , and Rhodospirillaceae were also enriched in the soils of genotypes like 8503 that were most effective in obtaining N from the corn residue, and this was correlated with greater potential expression of genes responsible for β-glucosidase and nitrification activity. Conclusions Carrot genotypes do differ in their potential to alter soil bacterial communities and stimulate microbially-mediated decomposition of organic materials indicating that it may be possible to begin selecting for this important trait.

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

Evaluating the nitrogen-contaminated groundwater treatment by a denitrifying granular sludge bioreactor: effect of organic matter loading - Barbara Muñoz-Palazon; Alejandro Rodriguez-Sanchez; Miguel Hurtado-Martinez; Jesús Gonzalez-Lopez; Riku Vahala; Alejandro Gonzalez-Martinez (Environmental Science and Pollution Research, 2021)

Molecular characterization of KPC-2-producing Klebsiella pneumoniae ST258 isolated from bovine mastitis - Jesús Silva-Sanchez; Humberto Barrios-Camacho; Emmanuel Hernández-Rodriguez; Josefina Duran-Bedolla; Alejandro Sanchez-Perez; Luary C. Martínez-Chavarría; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro; Ulises Garza-Ramos (Brazilian Journal of Microbiology, 2021)

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Influence of salinity cycles in bioreactor performance and microbial community structure of membrane-based tidal-like variable salinity wastewater treatment systems - Alejandro Rodriguez-Sanchez; Juan Carlos Leyva-Diaz; Barbara Muñoz-Palazon; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2019)

Maximum Influent Salinity Affects the Diversity of Mineral-Precipitation-Mediating Bacterial Communities in Membrane Biofilm of Hybrid Moving Bed Biofilm Reactor-Membrane Bioreactor - Alejandro Rodriguez-Sanchez; Barbara Muñoz-Palazon; Miguel Hurtado-Martinez; Maria Angustias Rivadeneyra; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Water, Air, & Soil Pollution, 2018)

Detection of comammox bacteria in full-scale wastewater treatment bioreactors using tag-454-pyrosequencing - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; M. C. M van Loosdrecht; Jesus Gonzalez-Lopez; Riku Vahala (Environmental Science and Pollution Research, 2016)

Impact of methionine on a partial-nitritation biofilter - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; Maria Jesus Garcia-Ruiz; Francisco Osorio; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2016)

Detection of sequences from a potentially novel strain of cell fusing agent virus in Mexican Stegomyia (Aedes) aegypti mosquitoes - Francisco Espinoza-Gómez; Alejandro U. López-Lemus; Irám P. Rodriguez-Sanchez; Margarita L. Martinez-Fierro; Oscar A. Newton-Sánchez; Edgar Chávez-Flores; Iván Delgado-Enciso (Archives of Virology, 2011)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)